Varicella challenges: A case of respiratory tract complications in an elderly patient - Rahmi, Alfina M.; Prakasita, Karine A.; Damayanti, Damayanti (Narra J, 2024)
Varicella, caused by the varicella-zoster virus (VZV), is rarely reported in the elderly but often complicates with pneumonia. In this case report, we present a case of varicella pneumonia in the elderly. A 60-year-old man presented to the emergency room with vesicles filled with clear fluid that had appeared all over the body for the past four days. The patient also reported fever, headache, pain when swallowing, and itching. Initially, the rash consisted of pink macules that progressed to papules, vesicles, pustules, and crusts. The patient experienced a cough and shortness of breath one day before the hospital visit but did not report any chest or abdominal pain. Notably, the patient’s two grandchildren had a history of chickenpox. The patient had been living with diabetes for five years and was undergoing treatment with insulin injections. The patient was also an active smoker for 40 years. On physical examination, several vesicles with varying degrees of redness were observed, along with yellow-black crusts, pustules, and erosions. Diagnostic tests revealed multinucleated giant cells on a Tzanck smear; pulmonary inflammation with thickening of the right hilum on a chest X-ray; extended-spectrum beta-lactamases Klebsiella pneumoniae in the sputum culture; and elevated hemoglobin A1c, blood sugar level, and liver and kidney function markers on laboratory examination. Based on the clinical findings, the patient was diagnosed with varicella, community-acquired pneumonia, diabetes, acute renal failure, and elevated transaminase enzymes. The patient was treated with acyclovir, paracetamol, salicylate 2% powder, fusidic acid 2% cream, moxifloxacin, N-acetylcysteine, curcuma, and insulin. The patient’s clinical condition improved, the complaint of dyspnea decreased, and the patient was discharged to outpatient care after eight days of hospitalization. This case highlights that while varicella is rare in the elderly, it often presents with severe varicella pneumonia, making early detection and comprehensive management essential to prevent complications and mortality.